Efeito da nistatina sobre a eficácia da clorexidina contra Streptococcus mutans em suspensão e biofilme polimicrobiano : estudo in vitro - Baldino, Maria Eduarda Lanes (2020)
Chlorhexidine and nystatin are drugs widely used to treat infections that affect the oral cavity. In some clinical situations, the drugs have been prescribed simultaneously, which, according to some authors, could interfere with their efficacy. The present study aimed to evaluate, in vitro, the effect of combined use of chlorhexidine and nystatin on the antibacterial action of chlorhexidine against Streptococcus mutans in suspension and in biofilm associated with Candida albicans. After using different combinations of the drugs with different time intervals in between, the minimum inhibitory concentration (MIC) of chlorhexidine was obtained by the broth microdilution method, and the effect on the biofilm was evaluated by crystal violet colorimetric assay (optical density=OD) and colony forming units (UFCs) counting. According to the results, nystatin/chlorhexidine combinations, except for 30-min interval groups, increased the MIC of chlorhexidine against S. mutans. In the biofilm analysis, the use of the drugs in a combined manner did not significantly differ from chlorhexidine group. However, among the combinations used, nystatin/2 min/chlorhexidine exhibited the lowest OD. The results suggest that chlorhexidine/nystatin combined, when administered in mixed biofilm of S. mutans and C. albicans, interferes more in the efficacy of nystatin than chlorhexidine. Among the combinations, the administration of nystatin before chlorhexidine seems to have the least interference in efficacy of the treatment. Conclusion: The combined use of chlorhexidine/nystatin can interfere with the antibacterial effect of chlorhexidine on S. mutans. The intensity of this interference depends on the concentration and time interval of the drugs and the lifestyle of the microorganisms (suspension or biofilm).